Enhancing Writing Skill through Inquiry-Based Teaching to the Eleventh Graders of SMA Kebakkramat State School in the Academic Year 2009-2010 - SURANTA , SURANTA (2011)
`Students of eleventh grade for science program at SMA Kebakkramat State School had a problem dealing with the writing skill. The problem was that they could not generate their idea into well structured composition. Their problems in writing were caused by as a result of lack of knowledge about the process of writing. They lack in the content, organization, and the most crucial one is about the discourse aspect. The research was carried out to maximize the students' ability to write English text. Hopefully, Inquiry-based Teaching strategy can enhance writing skill of the eleventh grade students of SMA Kebakkramat State School. The data was gained through several techniques. The qualitative data were collected through the observation, interview and questionnaire from the students' participation during the writing class. The qualitative data was gained from the observation of the documents as the results of the students' participation during the discussion when the strategy was implemented. It is carried out in order to know the effectiveness of Inquiry-Based Teaching strategy in overcoming the weakness, the problems of writing skill in the class. The quantitative data was gained from the writing assessment. The aspects of writing to be analyzed were content, organization, discourse, vocabulary, and mechanic. The research finding shows that Inquiry-Based Teaching strategy gives some positive effects toward the students' writing problems. The first, it can improve the students' motivation in learning English, especially writing skill. The second, it can influence the students' attitudes toward the teaching learning English process. The third, it improves the students' participation during writing class. And the last, it can improve the students' skill in writing English text. The implication of implementing the Inquiry-Based Teaching strategy to the writing class is that it can be an alternative technique to improve the students' writing English text skill. Thus, it is suggested that the English teacher should apply it in order to overcome the problem if they get the same problem as the researcher does. It is necessary for the institution to socialize it to the other teachers and students. The last, it is for the other researchers to use this research to develop the aspects that have not been touched.